2015
DOI: 10.1080/09540121.2015.1020280
|View full text |Cite
|
Sign up to set email alerts
|

Substance-use and sexual harm reduction strategies of methamphetamine-using men who have sex with men and inject drugs

Abstract: Research indicates that men who have sex with men (MSM), use methamphetamine, and inject drugs are at high risk of HIV infection and they employ multiple harm reduction strategies simultaneously to reduce that risk. In this study, we identified substances most commonly injected and harm reduction strategies most often employed by methamphetamine-using MSM, used latent class analysis (LCA) to identify patterns of harm reduction strategies, and differentiated MSM within each class by individual characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In particular, classes with stimulant smoking were more likely to report inconsistent condom use [34], transactional sex [14] and sexual risk-taking [18,19]. Similarly, studies of drug use among men who have sex with men in the USA and Malaysia [35][36][37][38] also found that polydrug using classes were more likely to report unsafe sexual behaviours in comparison with low or single substance use classes. In our prior analysis with an earlier cohort of PWID in Tijuana, we found that a small class (6%) defined by use of heroin, methamphetamine and cocaine exhibited higher-risk sexual practices.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, classes with stimulant smoking were more likely to report inconsistent condom use [34], transactional sex [14] and sexual risk-taking [18,19]. Similarly, studies of drug use among men who have sex with men in the USA and Malaysia [35][36][37][38] also found that polydrug using classes were more likely to report unsafe sexual behaviours in comparison with low or single substance use classes. In our prior analysis with an earlier cohort of PWID in Tijuana, we found that a small class (6%) defined by use of heroin, methamphetamine and cocaine exhibited higher-risk sexual practices.…”
Section: Discussionmentioning
confidence: 94%
“…Such approaches facilitate effective messaging and program design, especially in populations made up of diverse subgroups such as in men who have sex with men (MSM). Tailoring HIV prevention interventions to specific subgroups of MSM is particularly common and has led to interventions targeting young [2, 3], ethnic minority [4, 5], or drug using [6, 7] MSM. Empirical methods to characterize population heterogeneity are also critical for meaningful modeling of disease dynamics, outcomes of which are highly sensitive to assumptions about population structure and subgroup interactions [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…The predilection for methamphetamine or mephedrone uses in slamming depends on the country and on the drug-use patterns in the gay community of each country explored. For example, methamphetamine is almost absent in France or only sold in Paris at very high prices, explaining the preferential use of stimulants such as cathinones in the practice of slam, while methamphetamine is widely available in the USA [8, 9, 55, 56], Australia [10, 32], and Asia [5, 7, 30]. Therefore, slam is not necessarily associated with NPS in all countries, and its emergence is closely linked to the availability of cathinones and the appearance of mephedrone in 2007.…”
Section: Discussion/conclusionmentioning
confidence: 99%